Method for energy scale calibration of the scintillation detector at registration of recoil protons - Bozhko, V.P.; Vodin, A.N.; Olejnik, S.N.; Tuller, G.E. (Functional Materials, 2009)
A method of the energy scale calibration of scintillation detectors in the proton energy range 1 to 14 MeV has been developed. The method is based on comparison of maxima of calculated and experimental spectra of recoil protons obtained due to scattering of quasimonochromatic neutrons from the d(T,n)⁴He and d(D,n)³He reactions on hydrogen nuclei contained in the converter. The energy scale calibration of a Csl(Tl) detector has been carried out using the d(T,n)⁴He reaction. It is found that the proton energy dependence of the detector specific light yield has a square polynomial form.